2004
DOI: 10.2116/analsci.20.1165
|View full text |Cite
|
Sign up to set email alerts
|

Neutral-Carrier-Type Potassium Ion-Selective Electrodes Based on Polymer-supported Liquid-Crystal Membranes for Practical Use

Abstract: Potentiometric ion sensors, such as neutral-carrier-type ionselective electrodes (ISEs), are very useful. 1 The ion selectivities are generally determined by the ion-exchange equilibrium at the interface between the membrane and the aqueous sample phases, which is in turn the metal-ion extraction equilibrium between the two immiscible phases. 2The ion selectivity for liquid-membrane ion sensors based on neutral carriers is often governed by the ion selectivity of the neutral carriers in the membrane. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The proposed K + ISE exhibits good selectivity compared with previously described sensors 8,[22][23][24][25][26] (Table 3). It exhibits a better working concentration range, slope and potentiometric selectivity for K + over many cations.…”
Section: Potentiometric Selectivitymentioning
confidence: 75%
“…The proposed K + ISE exhibits good selectivity compared with previously described sensors 8,[22][23][24][25][26] (Table 3). It exhibits a better working concentration range, slope and potentiometric selectivity for K + over many cations.…”
Section: Potentiometric Selectivitymentioning
confidence: 75%
“…In the case of compound 3, which is able to form a nematic liquid crystal phase, it was not possible to observe the surface of membranes due to the high fluidicity. Therefore, compound 4, which is able to form a less fluidic phase (smectic liquid crystal), was employed here as the membrane solvent, because it possesses similar structural and sensor properties 4,5 to those of compound 3. The content of compound 2 in the membranes was 5.0 wt%, because no clear AFM images were observed when the content of compound 2 was 1.0 wt%.…”
Section: Afm Imagesmentioning
confidence: 99%
“…We have previously reported that thermotropic liquidcrystalline compounds for membrane solvents of ISEs have conferred a high functionality on membrane ion sensors. [3][4][5][6] Liquid crystals are functional materials, because their molecular orientation varies in response to changes in temperature, light, electric field, etc. Thus, the ion-sensor property could be controlled by the orientation of the membrane components in liquid-crystalline compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Oosaki S. and colleagues prepared two types of liquid crystal potassium ion selective electrodes. While for one type microporous PTFE (polytetrafloroethylene) was used, for the second one PMMA (polymethilmethacrylate and a derivative of benzo-15-crown-5-ether as neutral carrier [40] was used. Sungeun Kim and et al stated that PVC membrane electrode for selective potassium ion could be prepared by using 1,3-alternate calix [4] crown-5-azacrown-5 ether [41].…”
Section: Introductionmentioning
confidence: 99%